Telomere length and genetics are independent colorectal tumour risk factors in an evaluation of biomarkers in normal bowel. - Fernandez-Rozadilla, C; Kartsonaki, C; Woolley, C; McClellan, M; Whittington, D; Horgan, G; Leedham, S; Kriaucionis, S; East, J; Tomlinson, I (Nature Publishing Group, 2018)
Background Colorectal cancer (CRC) screening might be improved by using a measure of prior risk to modulate screening intensity or the faecal immunochemical test threshold. Intermediate molecular biomarkers could aid risk prediction by capturing both known and unknown risk factors. Methods We sampled normal bowel mucosa from the proximal colon, distal colon and rectum of 317 individuals undergoing colonoscopy. We defined cases as having a personal history of colorectal polyp(s)/cancer, and controls as having no history of colorectal neoplasia. Molecular analyses were performed for: telomere length (TL); global methylation; and the expression of genes in molecular pathways associated with colorectal tumourigenesis. We also calculated a polygenic risk score (PRS) based on CRC susceptibility polymorphisms. Results Bowel TL was significantly longer in cases than controls, but was not associated with blood TL. PRS was significantly andindependently higher in cases. Hypermethylation showed a suggestive association with case:control status. No gene or pathway was differentially expressed between cases and controls. Gene expression often varied considerably between bowel locations. Conclusions PRS and bowel TL (but not blood TL) may be clinically-useful predictors of CRC risk. Sample collection to assess these biomarkers is feasible in clinical practice, especially where population screening uses flexible sigmoidoscopy or colonoscopy.